Recycling and screening of agricultural wastes to reuse in biofloculated aquaria inhabiting Ctenopharyngodon idella - Komal Tayyab; Sumaira Aslam; Faiza Jabeen; Tamseela Mumtaz; Zill-i- Huma; Meerab Aziz (International Journal of Recycling of Organic Waste in Agriculture, 2025)
Purpose: This study was conducted in the context to recycle the agricultural wastes among fruits and vegetable peels in a biofloc system inhabiting grass carp fingerlings (Ctenopharyngodon idella). Fish has attained a vital place in the food industry, but the major problem is costly fish feed along with water management.